Lobar Radioembolization for Intermediate and Advanced Hepatocellular Carcinoma: Retrospective and Prospective Data - Lakhoo, Janesh; Perez, Thomas H.; Borgmann, Anthony J.; Brown, Daniel B. (Seminars in Interventional Radiology, 2021)
Historically, outcomes reporting for radioembolization with yttrium-90 (90Y) of hepatocellular carcinoma has included patients across the range of Barcelona Clinic Liver Cancer (BCLC) stages. With the potential for curative radiation segmentectomy for BCLC 0/A patients and evolution of systemic therapy for BCLC C patients, focused review by group is of increasing interest. In this review, we report on efficacy of 90Y in patients with intermediate (BCLC B) and advanced (BCLC C) hepatocellular carcinoma as well as expected toxicities. Additionally, we review existing trials comparing 90Y to transarterial chemoembolization and systemic treatments in these patient groups and outline future studies.
Keywords: hepatocellular carcinoma; Barcelona Clinic Liver Cancer; radioembolization; chemoembolization; interventional radiology